Rare Congenital Aberrant Left Superior Pulmonary Vein Discovered with Central Line Placement in a Patient with Critical Cardiorespiratory Collapse - Spencer Knox; Mario Madruga; S. J. Carlan (Case Reports in Pulmonology)
Background. Partial anomalous pulmonary venous connection is a rare congenital vascular disorder that may be asymptomatic. Left-sided connections with the innominate vein are discovered infrequently and those without an atrial septal defect are extremely rare. Case. A 66-year-old male was found to have an anomalous left pulmonary vein when a central venous catheter was inserted for management of hypoxemia. In addition to the connection with the left innominate vein an echocardiogram revealed no atrial septal defect. Computed tomography arteriography was used to define the anomaly. Conclusion. Left superior vein partial anomalous pulmonary venous connection with the left innominate vein was discovered incidentally on insertion of central venous catheter. The otherwise innocuous anomaly can become a significant variable when treating critical cardiopulmonary collapse.